2022
DOI: 10.3390/diagnostics12123067
|View full text |Cite
|
Sign up to set email alerts
|

Using Recurrent Neural Networks for Predicting Type-2 Diabetes from Genomic and Tabular Data

Abstract: The development of genomic technology for smart diagnosis and therapies for various diseases has lately been the most demanding area for computer-aided diagnostic and treatment research. Exponential breakthroughs in artificial intelligence and machine intelligence technologies could pave the way for identifying challenges afflicting the healthcare industry. Genomics is paving the way for predicting future illnesses, including cancer, Alzheimer’s disease, and diabetes. Machine learning advancements have expedit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…To ensure the security of the data shared across the unsecured channel using the socket layer (SSL), the data's privacy is enforced through two‐factor authentication. MongoDB, a NoSQL database, stores the corresponding user data 46,47 . If the technology described above were implemented, the future view paradigm would be replaced with a user‐centric system that includes all the essential components.…”
Section: Experimentation Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure the security of the data shared across the unsecured channel using the socket layer (SSL), the data's privacy is enforced through two‐factor authentication. MongoDB, a NoSQL database, stores the corresponding user data 46,47 . If the technology described above were implemented, the future view paradigm would be replaced with a user‐centric system that includes all the essential components.…”
Section: Experimentation Results and Analysismentioning
confidence: 99%
“…MongoDB, a NoSQL database, stores the corresponding user data. 46,47 If the technology described above were implemented, the future view paradigm would be replaced with a user-centric system that includes all the essential components.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…RNNs are a sort of neural network that uses previous data from a time series to make predictions about the future [15]. Recurrent Neural Networks (RNNs) function based on the principle of retaining the output of a particular layer and reintroducing it as input in order to predict the output of that layer.…”
Section: Multiple Layer Rnn In Sapfmentioning
confidence: 99%
“…They used several text mining and machine learning strategies to perform sentiment analysis on distributed LSTM framework and ran it in three different corpora, and the results showed that they were superior to some machine learning methods such as LDA and SVD in accuracy and efficiency. Srinivasu et al [39] used recurrent neural networks such as LSTM and GRU to predict type 2 diabetes. At the same time, some scholars introduced the attention mechanism [40] into the application fields such as sentiment analysis and text classification, and the results indicate that attention mechanism is of great significance.…”
Section: Plos Onementioning
confidence: 99%